Wear-resistant coatings for thermal interfaces

By using a thermally conductive film formed of silicone resin-containing filler and an inorganic particle filler between the pluggable electronic component and the heat dissipation device, the problem of insufficient wear resistance of the thermal interface material in the prior art is solved, and the effects of low thermal resistance and high wear resistance are achieved.

CN112771662BActive Publication Date: 2025-04-04HENKEL KGAA
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
CN201980063409.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-27
Filing Date
2019-09-27
Publication Date
2025-04-04
Estimated Expiration
2039-10-06

AI Technical Summary

Technical Problem

The prior art is difficult to establish an wear-resistant thermal interface material between the pluggable electronic components and the heat dissipation device, resulting in an increase in thermal resistance and unable to withstand the frictional force of repeated installation and removal.

Method used

A thermally conductive film formed of silicone-containing resin and inorganic particle filler is used, which has conformability and wear resistance, and is applied on the surface of the metal substrate and cured in situ to form an interlocking polymer network to enhance adhesion and wear resistance.

Benefits of technology

The thermal resistance between the pluggable electronic components and the heat dissipation device is effectively reduced, and the wear resistance is maintained during repeated installation and removal, with the thermal resistance increasing by no more than 50%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112771662B_ABST
    Figure CN112771662B_ABST
Patent Text Reader

Abstract

A system with removable electronic components uses a wear-resistant thermally conductive film as a thermal interface between the removable electronic components and a heat sink. When the removable electronic components are repeatedly installed and removed from a chamber in a host device, the wear-resistant film reduces the thermal resistance between the removable electronic components and the heat sink. The wear-resistant film includes a polymer formed of a silicone-containing resin and an inorganic particle filler, and the film can also interlock with an anti-corrosion layer at the heat sink. A method for forming a heat sink is provided, the method minimizing the increase in thermal resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermally conductive film as a thermal interface between a heat generating device and a heat sink. More specifically, the present invention relates to a wear-resistant thermally conductive film that reduces the thermal resistance between the heat generating device and the heat sink, thereby allowing the heat generating device to be repeatedly installed and removed. Background Art

[0002] Electronic systems increasingly rely on faster speeds and greater capacity in smaller packages. In addition, electronic systems continue to employ increasingly complex arrays of electronic devices, including modular arrays that can operate with a variety of replaceable components. Examples of replaceable components include optical transceivers such as C-form-factor pluggable (CFP) optical transceivers and small form-factor pluggable (SFP) optical transceivers that can be installed in or removed from modular systems. Such optical transceivers are "pluggable" because they can be inserted into and removed from a host device or system without cutting off the power supply to the host device or system. Pluggable transceivers are typically received in chambers or ports defined by the various frames of the host system.

[0003] In order to prevent heat from accumulating in the pluggable electronic components, a heat sink can be used at and / or around the receiving chamber to help dissipate the generated heat from the pluggable electronic components. In a typical embodiment, when installed in the chamber, the heat sink contacts the pluggable electronic components so that heat can be dissipated from the pluggable electronic components in a conductive manner. The efficiency of conductive heat transfer from the pluggable electronic components to the heat sink is largely limited by the thermal resistance of the interface between the pluggable electronic components and the heat sink. Typically, non-contact in a portion of the interface hinders heat transfer, so that the heat transfer performed by conduction is limited to that part of the contact area of ​​each surface where the pluggable electronic device and the heat sink contact. Typically, the contact surface is an uneven metal. The uneven surface is combined with the surface stiffness to prevent extensive physical contact between the surfaces.

[0004] One method of reducing thermal resistance at the interface between metal surfaces is to coat at least one of the metal surfaces with a compliant or conformable thermal interface material, such as a paste, gel, film, or the like. Such conformable thermal interface materials, while effective in static applications of pluggable electronic components and associated heat sinks, cannot withstand the frictional forces generated in dynamic settings, such as pluggable electronic components, where the pluggable electronic components are repeatedly slid into and out of a chamber in frictional contact with a heat sink. As a result, these conformable thermal interface materials can disintegrate over time due to repeated installation and removal of the pluggable electronic components. Degradation of the thermal interface material results in an increase in the thermal resistance to heat transfer from the pluggable electronic component to the heat sink.

[0005] Therefore, there is a need for a thermal interface material applied to the interface between a pluggable electronic component and a heat sink that is not only sufficiently conformable to reduce the thermal resistance of the interface, but also has abrasion resistance to withstand repeated installation and removal of the pluggable electronic component from a host device in contact with the heat sink. Ideally, this abrasion resistance includes both the cohesion of the thermal interface material and the adhesion of the thermal interface material to a corresponding surface, such as the surface of the heat sink. Summary of the invention

[0006] A system is disclosed herein, comprising: a frame defining a cavity; a heat sink; and a removable electronic component that is removably inserted into the cavity to thermally contact a heat transfer region of the heat sink. The heat sink comprises a metal substrate having a first surface and a second surface defining a thickness therebetween, the metal substrate having a substrate thermal resistance; a thermally conductive film disposed on at least a portion of at least one of the first surface or the second surface, the thermally conductive film defining a heat transfer region, the thermally conductive film comprising (1) a polymer formed from a silicone-containing resin and (2) an inorganic particulate filler. An initial thermal resistance across the thickness of the heat transfer region is defined before a Taber abrasion test, and an abrasion thermal resistance across the thickness of the metal substrate is defined after the Taber abrasion test is completed, wherein the abrasion thermal resistance is greater than about 50% greater than the initial thermal resistance.

[0007] Another embodiment discloses a system comprising: a host device including a frame defining a chamber; a removable module generating heat that is transferred to a first surface of the module, the module being removably mounted in the host device via the chamber; and a heat sink associated with the frame to dissipate heat from the first surface. The heat sink includes a second surface, a thermally conductive film is applied to the second surface to define a heat transfer area of ​​the heat sink, and wherein the thermally conductive film is applied to at least a portion of the first surface or the second surface to define the heat transfer area of ​​the heat sink, and wherein when the module is mounted in the device, the thermally conductive film is in direct contact with the first surface or the second surface to allow heat to be received from the first surface. The system exhibits an initial thermal resistance through the heat transfer area before Taber abrasion testing and an abrasion thermal resistance through the heat transfer area after the Taber abrasion testing is completed, the abrasion thermal resistance being no more than about 50% greater than the initial thermal resistance.

[0008] In yet another embodiment, a system is disclosed, wherein the system includes a host device, the host device including a frame defining a chamber; a removable module, the removable module generating heat, the heat being transferred to a first surface of the module, the module being removably mounted in the host device via the chamber; a heat sink associated with the frame to dissipate heat from the first surface. The heat sink includes a second surface, and a thermally conductive film applied to the first surface or the second surface. When the module is mounted in the device, the thermally conductive film is in direct contact with the first surface to allow heat to be received from the first surface, the second surface includes a corrosion protection layer, and the thermally conductive film includes a silicon-containing polymer interlocked with the corrosion protection layer.

[0009] In yet another embodiment, a method for forming a heat sink is provided, the method comprising: providing a metal substrate having a first surface, treating the first surface with a conversion agent to form a corrosion protection layer, preparing a precursor having a silicon-containing resin and an inorganic particulate filler, coating the precursor on the corrosion protection layer and curing in situ to polymerize the precursor. The silicon-containing polymer formed from the resin interlocks with the corrosion protection layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 A schematic cross-sectional view of a system of the present invention is depicted with a removable module installed in a host device.

[0011] Figure 2 A schematic cross-sectional view of a system of the present invention is depicted with a removable module installed in a host device.

[0012] Figure 3 A flow chart depicting the steps for coating a metal substrate with a thermally conductive film.

[0013] Figure 4Plotted are the absolute mass loss of the films from their respective metal substrates after Taber abrasion testing.

[0014] Figure 5 The relative mass loss of the films from their respective metal substrates after Taber abrasion testing is shown graphically.

[0015] Figure 6 Plotted are the absolute mass loss of the films from their respective metal substrates after Taber abrasion testing.

[0016] Figure 7 The relative mass loss of the films from their respective metal substrates after Taber abrasion testing is shown graphically. DETAILED DESCRIPTION

[0017] The present invention relates to a removable electronic component suitable for interacting with a host device when installed in the host device. The removable electronic component is installed in the host device and removed from the host device by slidable engagement and disengagement with a heat sink. The heat sink is usually located in a chamber / receptacle of the host device so that the installation of the removable electronic component brings the removable electronic component into thermal contact with the heat sink. Thermal contact is established through a thermal interface between the removable electronic component and the heat sink. The thermal interface is at least partially filled by a thermal interface member of the present invention. The thermal interface member can preferably be a wear-resistant and cohesive body in the form of a film or coating. The thermal interface member can be adhered to a heat transfer surface that can be part of the heat sink or thermally connected to the heat sink. The removable electronic component is installed in the chamber / receptacle of the host device so that the heat transfer surface of the removable electronic component is in thermal contact with the thermal interface body that is itself connected to the heat sink.

[0018] As used herein, the term "host device" is intended to refer to a computer or computing device, a network device, a signal transmitter, a signal receiver, a switch, a data storage device, a subsystem, a printed circuit board, an integrated circuit, a microprocessor, and the like.

[0019] Figure 1 and 2 A schematic cross-sectional view of an exemplary system 10 of the present invention is depicted. Figure 1 , a removable module 12 is shown being installed into a chamber 14 of a host device 16 along directional arrow 13. Figure 2A system 10 is shown having a removable module 12 mounted at a host device 16. The removable module 12 may have a first surface 12a to which heat generated by the removable module 12 is transferred. It is contemplated that heat generated by the removable module 12 may be transferred to portions of the removable module 12 in addition to the first surface 12a, but for purposes of this description, heat dissipation is directed to the host device 16 via the first surface 12a. The removable module 12 may be, for example, a pluggable optical transceiver.

[0020] The system 10 includes a heat sink 20 for dissipating heat from the removable module 12 through the first surface 12a. The heat sink 20 may be associated with the frame 15 of the host device 16. The heat sink 20 is generally made of a material with high thermal conductivity (such as metal, metal alloy, etc.) and may include one or more heat dissipation devices that effectively dissipate the heat generated by the removable module 12. Figure 1 In the illustrated embodiment, the heat sink 20 may include a plate portion 22 and heat sink fins 24 extending from and thermally coupled to the plate portion 22. The heat sink 24 provides an increased surface area to enhance the transfer of heat to a cooling medium such as, for example, ambient air (not shown) in contact with the heat sink 24. The heat sink 20 may be made of a variety of thermally conductive materials, examples of which include, but are not limited to, aluminum and copper. The plate portion 22 of the heat sink 20 includes a heat receiving surface 26 for receiving heat from the removable module 12.

[0021] Preferably, a thermally conductive film 30 is applied to the heat receiving surface 26 to define a heat transfer area "A" where heat from the removable module 12 is most efficiently transferred to the heat sink 20 through the thermally conductive film 30. Such a heat transfer area "A" reduces the thermal resistance to the heat sink 20. The heat transfer area "A" can be any size, preferably about 0.5-1.5 cm 2 , more preferably about 1.0 cm 2 .

[0022] The thickness "T" between the heat receiving surface 26 and the heat dissipating surface 28 is defined. Figure 1 As shown, Figure 2 When removable module 12 is mounted as shown, heat sink 20 and thermally conductive film 30 may be mounted to frame 15 in a manner that causes contact with first surface 12a of module 12. This contact allows heat sink 20 to receive heat generated by removable module 12 and dissipate it in an appropriate manner.

[0023] When the module 12 is mounted in the chamber 14 of the host device 16, the thermally conductive film 30 is thermally coupled to the first surface 12a of the module 12, preferably in direct contact with the first surface 12a of the module 12. Therefore, the thermally conductive film 30 is located at the thermal interface between the module 12 and the heat sink 20. In this way, the module 12 is thermally coupled to the heat sink 20 via the thermally conductive film 30.

[0024] The thermally conductive film 30 is conformable, deformable and / or flexible to fill the gap between the first surface 12a of the removable module 12 and the heat receiving surface 26. Therefore, the thermally conductive film 30 is used to fill the gap space between the first surface 12a of the removable module 12 and the heat receiving surface 26 of the heat sink 20, which would otherwise significantly hinder heat transfer. As a result, the thermally conductive film 30 forms a part of the heat transfer path between the removable module 12 and the heat dissipation surface 28 / heat dissipation fins 24. A heat transfer path is established to transfer heat to the heat receiving surface 26 by conduction from the first surface 12a via the thermally conductive film 30.

[0025] In order to effectively fill the gap space at the interface between the removable module 12 and the heat sink 20, the thermally conductive film 30 preferably exhibits a relatively low elastic / Young's modulus and a relatively low flexural modulus. In some embodiments, the elastic / Young's modulus of the thermally conductive film 30 is less than about 10 MPa, more preferably less than about 1 MPa, and rebounds greater than about 95% after compression according to ASWTM-D395. The flexibility / deformability of the thermally conductive film 30 can be adjusted by changing its shape or thickness. In some particularly useful embodiments, the thermally conductive film 30 is formed with a substantially uniform thickness ("T f ”) application.

[0026] The thermally conductive film 30 is thermally conductive, conformable, and wear-resistant, so that the thermally conductive film 30 is durable in applications where the removable module 12 is repeatedly installed and removed from the chamber 14 of the host device 16 as described above. The removable module 12 is typically installed and reinstalled in a manner that slides in physical contact with the thermally conductive film 30. Therefore, damage to the thermally conductive film 30 due to such repeated installation and removal can significantly increase the thermal resistance at the interface between the first surface 12a of the module 12 and the heat receiving surface 26 of the heat sink 20. Therefore, it is important that the thermally conductive film 30 must also be wear-resistant due to the sliding contact between the module 12 and the thermally conductive film 30. In some embodiments, the thermally conductive film 30 may exhibit a thermal conductivity of at least about 0.1 W / m·K, and more preferably at least about 0.5 W / m·K, which is increased by the thickness T of the thermally conductive film 30. f Measurement.

[0027] The thermally conductive film 30 is preferably formed of one or more polymer-forming resins and one or more inorganic particulate fillers. In some embodiments, the polymer-forming resin is a silicon-containing thermosetting resin. Exemplary thermosetting resin compositions contemplated for use in the thermally conductive film 30 include epoxy compounds, acrylates, and polyurethanes. Other examples of polymer-forming resins useful in the thermally conductive film 30 of the present invention are described in U.S. Patent Nos. 5,028,984 and 3,908,040, the entire contents of which are incorporated herein by reference.

[0028] In one exemplary embodiment, the crosslinked polymer network is formed from a two-component type platinum catalyzed addition-cured silicone polymer using a vinyl terminated polydimethylsiloxane reacted with a methylhydrogensiloxane-dimethylsiloxane, trimethylsiloxy terminated copolymer.

[0029] The thermally conductive film 30 also includes an inorganic particle filler. In some embodiments, the inorganic particle filler is selected from alumina, diamond, clay, aluminosilicate, aluminum nitride, boron nitride, aluminum oxide, aluminum nitride, magnesium oxide, zinc oxide, silicon carbide, silicon dioxide, beryllium oxide, antimony oxide, and combinations thereof. In a particularly useful embodiment, the inorganic particle filler is aluminum nitride. In another embodiment, the filler is selected from carbon nanotubes, graphene, fullerene, and graphite.

[0030] The inorganic particle filler can be added to the resin forming the polymer at a concentration of less than about 300 (phr) parts / 100 parts of resin, more preferably less than about 150phr. It is surprisingly determined that the concentration of the inorganic particle filler is less than or equal to 50phr, which provides the benefit of enhancing the wear resistance of the thermally conductive film 30. As described in more detail below, the reduction of the inorganic particle filler loaded into the thermally conductive film 30 reduces the degradation of the thermally conductive film after the wear test, and therefore minimizes the increase in thermal resistance at the heat transfer area "A" after the wear test. It is believed that the lower particle filler concentration reduces the interference of the polymer matrix with the adhesion of the metal substrate. As a result, the lower particle filler concentration can allow a "tougher" cross-linked polymer that exhibits enhanced wear resistance. Even if there are less inorganic fillers in the thermally conductive film 30, this enhanced wear resistance still maintains a lower thermal resistance after the wear resistance test. Surprisingly, compared with the film that itself may have a higher thermal conductivity due to the higher inorganic particle filler concentration level, the wear resistance and the continuity of the polymer matrix are better maintained while maintaining low thermal resistance.

[0031] In some embodiments, the maximum particle size of the inorganic particulate filler may be less than about 50 μm, more preferably less than about 25 μm. In an exemplary embodiment, the average particle size of the inorganic particulate filler may be about 1-5 μm, more preferably about 3 μm.

[0032] A heat sink including a thermally conductive film 30 can be formed by applying a precursor to a heat receiving surface 26 of a plate portion 22 and curing the precursor in situ at the heat receiving surface 26. In a useful embodiment, the plate portion 22 includes a metal substrate having a first surface, such as the heat receiving surface 26 of the plate portion 22 of aluminum or copper. The present invention contemplates other metals or metal alloys, including metal coatings at the heat receiving surface 26. In some embodiments, the first surface of the metal substrate can be treated with a conversion agent to form a corrosion protection layer. The conversion agent can be at least one of hexavalent chromium, trivalent chromium, tin, titanium oxide, magnesium oxide, chromium-free Alodine, and zinc.

[0033] The precursor applied to the first surface of the conversion treatment of the metal substrate can include a silicon-containing resin and an inorganic particle filler, wherein the silicon-containing resin can be a resin that forms a polymer. Such a precursor can be less than 75 μm, preferably coated on the corrosion protection layer with a thickness of 10-50 μm. The precursor can be coated on the corrosion protection layer by screen printing, slit coating, dip coating, selective printing, curtain coating, slit die distribution or other suitable coating techniques. The precursor material can be liquid, pasty, gelatinous, greasy or other forms known as pre-cured states. In one embodiment, the precursor can be a solution in one or more solvents. The coated precursor can be cured in situ by an appropriate curing mechanism to polymerize the precursor, wherein the silicon-containing polymer formed by the resin is interlocked with the corrosion protection layer. The curing mechanism intended for use herein includes but is not limited to ultraviolet radiation, thermal radiation, ultrasonic treatment, chemical curing, etc.

[0034] The term "interlocking" herein is intended to mean a connection between a silicon-containing polymer and a corrosion protection layer that is at least partially related to a mechanical interlock as described in "Chemical Adhesion of Silicone Elastomers on Primed Metal Surfaces: A Comprehensive Survey of Open and Patent Literatures", Progress in Organic Coatings, Loic Picard et al., Vol. 80 (2015) pp. 120-141, the contents of which are incorporated herein by reference. An example of such a connection is coupling an organic silicone elastomer to a metal surface coated with a primer.

[0035] Reference now Figure 3Flow chart of is used to describe an exemplary method for forming a heat sink 20 incorporating a thermally conductive film 30. In order to provide the desired wear resistance, the thermally conductive film exhibits high cohesion, as well as a high level of adhesion to the metal heat receiving surface 26. In order to facilitate this adhesion, the heat receiving surface 26 can be treated to enhance the connection with the polymer film. The metal surface can be passivated to form a corrosion protection layer, which also acts as an interlock with the polymer of the thermally conductive film. Various metal surface treatments can be used to passivate the metal surface, including but not limited to anodization, chromate conversion, tinning and zinc plating. An example of a useful metal surface treatment is a chromate conversion coating using trivalent (type 1) or hexavalent (type 2) chromium (available from Henkel Corporation, Madison Heights, MI under the trademark Bonderite or Alodine).

[0036] Other useful metal surface treatments include those available from Henkel Corporation under the trade name EC 2 Electroceramic coatings are obtained and described in U.S. Patent Application Publication No. 2017 / 0121841, and metal surface treatments are described in U.S. Patent Nos. 6,946,401; 6,361,833; 4,162,947; and 3,434,943 and U.S. Patent Application Publication No. 2010 / 0038254, the entire contents of each of which are incorporated herein.

[0037] The treated metal heat sink is then immersed in a solvent such as isopropyl alcohol, acetone, alkanes or water and sonicated for 2-10 minutes. The metal heat sink is removed from the ultrasonic bath and dried using an ionized air gun (such as the "TopGun Static Elimination Gun" available from Simco-Ion) to reduce or eliminate static charges and particles on the metal surface.

[0038] After the ionized air drying step, the metal heat sink is treated with UV radiation and ozone to clean solvent residues, silicone oil or flux.

[0039] A precursor having a silicone resin and an inorganic particle filler is prepared and dispensed onto the corrosion protection layer prepared as described above. The precursor may be dispensed onto the corrosion protection layer of the passivated metal surface by screen printing or other small volume dispensing procedures such as slot coating, dip coating or selective printing. The coated heat sink is then baked in an oven at 25-200° C. for 1-240 minutes to cure / polymerize the precursor in situ.

[0040] The thermally conductive film composition according to the present invention may optionally further comprise one or more flow additives, adhesion promoters, rheology modifiers, toughening agents, fluxing agents, reaction rate modifiers, and the like and combinations thereof. An example of a reaction rate modifier is tetravinyltetramethylcyclotetrasiloxane. Examples or surface coupling agents / adhesion promoters for improving the adhesion of the film to a metal heat sink include epoxy-functional trimethoxysilane, vinyl-functional trimethoxysilane, and methacrylate-functional trimethoxysilane. Titanium (IV) butoxide may be used to catalyze the condensation of a silane coupling agent with a target substrate. Examples of toughening agents may include pyrogenic silica treated with hexamethyldisilazane.

[0041] Film composition

[0042] The following compositions are intended to be exemplary only and represent certain components that may be included in the film compositions of the present invention.

[0043] Example material 1 (for aluminum metal substrate)

[0044]

[0045] Example material 2 (for copper metal substrate)

[0046]

[0047] Wear resistance test

[0048] The wear resistance and thermal performance of the heat sink coated with the thermally conductive film of the present invention were tested. The test method called "Taber abrasion test" used in this article includes concepts from ASTM standards G133, F732, F2025, F2496 and D4060 to evaluate the wear resistance of the coating. Because the success of the film of the present invention depends on its wear resistance during repeated installation and removal from the host device, the Taber abrasion test attempts to quantitatively evaluate the performance of the film. Similar to the methods given in ASTM F732 and F 2496, the quantitative determination of wear resistance is the volume percentage of the coating film lost during the abrasion test. Similar to ASTM G133 and D4060, the volume loss can be determined gravimetrically by calculating the mass loss after abrasion. The original mass and the lost mass of the coating allow comparison of coatings with different densities.

[0049] A reciprocating grinder is available from Taber Industries as Model 5900. The Taber reciprocating grinder is equipped with a A general purpose cleaning pad served as the abrasive surface. An analytical balance capable of measuring to the nearest 0.1 mg was used to determine the mass of the loaded film and the mass loss after the abrasion test.

[0050] program

[0051] The film mass is determined by finding the difference between the mass of the coated substrate and the tare weight of the coated metal substrate. The sample to be ground is placed in the fixture of the reciprocating grinder and fixed firmly in place. A grinding pad with an area of ​​1 square inch is then brought into contact with the film and a force of 5N is applied. The reciprocating grinder is engaged and linear reciprocation is continued for the desired number of cycles at a rate of 60 cycles per minute. A reciprocating "cycle" as used herein includes two passes across the film surface, where each pass covers a stroke length of 80mm. In reference Figure 3 In the described procedure, each sample consisted of a film of Example Material 1 or Example Material 2 applied to a 1 inch x 4 inch aluminum lap.

[0052] After the reciprocating cycle is completed, the sample is removed from the fixture and all loose material / debris is removed with compressed air at 35 psi and wiped clean with a lint-free rag soaked in isopropyl alcohol. The ground sample is then dried and weighed to determine the mass loss of the membrane. When exposed to 400 cycles of the reciprocating grinder, any membrane mass loss of more than 20% is considered to be unacceptable for membrane durability. The samples are weighed after 50, 100, 200 and 400 passes.

[0053] result

[0054] Experiments were conducted using the Taber abrasion test technique on aluminum substrate samples coated with Example Material 1 but with varying concentrations of particulate filler. Figure 5 -8 shows the results of Taber abrasion testing conducted on samples incorporating 25, 50, 150 or 250 phr of aluminum nitride filler. Figure 5 -8 shows an unexpected benefit to abrasion resistance of films containing less than or equal to 50 phr of inorganic filler. The results are detailed in the "Relative Mass Loss" graph, which explains the relative mass loss after Taber abrasion testing, rather than just the absolute mass loss which can be affected by the initial mass of the film coating.

[0055] Thermal performance test

[0056] Abrasion resistance and durability were also tested by thermal performance, comparing thermal resistance before and after Taber abrasion testing. According to test method MET BASA #MET-5.4-01-1900-Test 2.1 at approximately 1.0 cm 2 A 50% increase in thermal resistance after the Taber abrasion test is considered unacceptable.

[0057] Example

[0058] The following samples were tested for wear resistance and thermal properties after Taber abrasion testing:

[0059]

[0060]

Claims

1. A system comprising: a host device, the host device comprising a frame defining a chamber; a removable module that generates heat that is transferable to a first surface of the module, the module being removably mounted in the chamber; A heat sink is associated with the frame to dissipate heat from the first surface, wherein the heat sink includes a second surface having a corrosion protection layer including at least one of trivalent chromium and hexavalent chromium and a thermally conductive film, the second surface having a corrosion protection layer including at least one of trivalent chromium and hexavalent chromium, the thermally conductive film including a silicon-containing polymer interlocked with the corrosion protection layer, and wherein when the module is installed in the device, the thermally conductive film is brought into direct contact with the first surface to allow heat to be received from the first surface. 2 . The system of claim 1 , wherein the thermally conductive film comprises an inorganic particulate filler and the silicon-containing polymer is formed from a silicon-containing resin.

3. The system of claim 2, wherein the inorganic particulate filler is present in the membrane at a concentration of less than or equal to 50 phr. The system of claim 3 , wherein the thermally conductive film reduces thermal resistance of a contact area between the heat sink and the first surface.

5. A method for forming a heat sink, comprising: providing a metal substrate having a first surface; treating the first surface with a conversion agent to form a corrosion protection layer comprising at least one of hexavalent chromium and trivalent chromium; preparing a precursor having a silicone-containing resin and an inorganic particulate filler; The precursor is coated on the corrosion protection layer and cured in situ to polymerize the precursor, The silicon-containing polymer formed from the resin is interlocked with the corrosion protection layer. 6 . The method of claim 5 , comprising applying the precursor on the corrosion protection layer by screen printing, slot coating, dip coating, selective printing, or a combination thereof. The method of claim 5 , wherein the silicon-containing polymer has a thickness of less than 25 μm.

8. The method of claim 5, wherein the inorganic particulate filler is present in a concentration of less than or equal to 50 phr.

Citation Information

Patent Citations

  • Tin electroplating solution and tin electroplating method

    US20100038254A1

  • Electroceramic Coating for Magnesium Alloys

    US20170121841A1

  • Anodizing process and additive for anodizing aluminum and its alloys

    US3434943A

  • Method of encapsulation

    US3908040A

  • Acid zinc plating baths and methods for electrodepositing bright zinc deposits

    US4162947A